Lacrimal gland inflammation is responsible for ocular pathology in TGF-beta 1 null mice. - McCartney-Francis, N. L. (1997)
Mice homozygous for a nonfunctional transforming growth factor-beta 1 gene develop rampant inflammation in vital organs that contributes to a shortened life span. The presence of circulating anti-nuclear anti-bodies, immune deposits in tissues, leukocyte infiltration, and increased major histocompatibility complex antigen expression resembles an autoimmune-like syndrome. One of the overt symptoms that appears in these mice lacking transforming growth factor-beta 1 is the development of dry crusty eyes that close persistently as their health declines. Histologically, the eyes appear normal with little or no inflammation. However, inflammatory lesions, predominantly lymphocytic, develop in the lacrimal glands, disrupting their structure and function and severely limiting their ability to generate tears. This histopathology and aberrant function mimic that of Sjögren's syndrome, a human autoimmune disease characterized by dry eyes and dry mouth. Impeding the leukocyte infiltration into the glands with synthetic fibronectin peptides, which block adhesion, not only prevents the inflammatory pathology but also prevents the persistent eye closure characteristic of these mice.